Modification of silica nanoparticles with 1-hydroxy-2-acetonaphthone as a novel composite for the efficient removal of Ni(II), Cu(II), Zn(II), and Hg(II) ions from aqueous media - Asma S. Al-Wasidi; Ahmed M. Naglah; Fawaz A. Saad; Ehab A. Abdelrahman (Arabian Journal of Chemistry, 2022)
In this paper, a novel composite based on the formation of Schiff base on silica nanoparticles was facilely synthesized. Firstly, silica nanoparticles, which contain silanol groups (Si-OH), were modified with (3-aminopropyl)trimethoxysilane. Then, the modified silica reacted with 1-hydroxy-2-acetonaphthone to form a novel Schiff base/silica composite. The synthesized composite was characterized using several tools such as XRD, FT-IR, FE-SEM, N2 adsorption/desorption analyzer, and CHN analyzer. The considerable reduction at 2θ = 21.9° in the intensity of the XRD peak of the composite is owing to the formation of the Schiff base. Also, the observed FT-IR bands in the composite at 3440 and 1604 cm−1 are owing to the stretching and bending vibrations of OH and/or CN, respectively. The FE-SEM images confirmed that the silica includes irregular shapes whereas the composite possesses a flaky surface owing to the formation of the Schiff base. Elemental analysis of the composite demonstrated that the % C, % H, and % N are 15.26, 3.24, and 1.65 %, respectively. The BET surface area and total pore volume of the composite were reduced because the formed Schiff base blocks the pores of silica. The synthesized composite was employed for the efficient removal of Ni(II), Cu(II), Zn(II), and Hg(II) ions from aqueous media. The maximum uptake capacity of the composite toward Cu(II), Hg(II), Zn(II), and Ni(II) ions is 68.630, 50.942, 45.126, and 40.420 mg/g, respectively. The adsorption processes of the studied metal ions were spontaneous, chemical, and well described using the pseudo-second-order kinetic model and Langmuir equilibrium isotherm. The synthesized composite can be successfully regenerated and utilized various times in the removal of studied metal ions from aqueous media.